Spectrophotometric Assay of Piperazine hexahydrate in Pharmaceutical Formulation with 3,5- Dinitrosalysilic Acid Reagent - Usra Al-Neaimy; USRA Al-Neaimy (مجلة التربية والعلم, 2020)
A simple spectrophotometric method for the determination of piperazine hexa- hydrate was developed. The method was based on the proton transfer reaction with 3,5- dinitrosalicylic acid (DNS) in basic solution to form yellow product showing a maximum absorbance at 410 nm with molar absorptivity of 8350 l/mol.cm . The method is obeyed Beer’s law over the concentration range 0.5-20 µg/ml. The average recovery % of the method is 99.12% and RSD % of the method is less than 2%. The method was applied for the determination of piperazine hexahydrate in pharmaceutical formulation as elixir and the results were in good agreement with the standard addition method .- - - - - - - - - - - - - - - - - - - - - - - - - - - - - -- - - - - - - - - - - - - - -